Wybór fotelika bezpieczeństwa do transportu dziecka - badania ankietowe - Frej Damian P.; Grabski Paweł (2024)
The greatest threat to the safety and health of a child placed in a safety seat is still the incorrectly chosen and installed seat in the vehicle. Safety seats are considered the primary means of reducing the risk of injury in a road accident. However, most parents use improperly installed seats. Improperly chosen and installed safety seats can pose a risk of injury to children in the event of an accident. The aim of the article is to improve the safety of children transported in safety seats by identifying and determining the impact of various, often non-obvious factors on the choice of safety seat made by parents/legal guardians of the child. To achieve this, a survey was conducted among a group of 950 individuals to understand the behaviors of parents and legal guardians related to the purchase of safety seats. Respondents were tasked with answering questions related to travel time, seat attachment location, or their personal preferences related to place of residence or age. It is worth noting that as many as 357 respondents would definitely not repurchase their current safety seat. Additionally, the level of safety of the seat determined by crash test results is an important purchasing argument for 21.88% of surveyed women and 35.66% of surveyed men.